Perbaikan User Experience Pada Aplikasi Mobile E-Commerce Tapp Market Menggunakan Metode Diary Study Dan User Journey - Muhammad Hanif; Hanifah Muslimah Az-Zahra; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
The development of technology at this time has entered various human activities, especially on the activities of buying and selling goods. With the presence of various technologies on the process of buying and selling goods such as mobile e-commerce applications that can already be used at this time facilitate the public in running the process of buying and selling goods online. Because there are enough applications that exist then each application must be able to compete with other applications. One of these applications is a mobile e-commerce application tapp market that entered in 2015 in Indonesia. Because the application is a new application launched in Indonesia it is necessary to evaluate and improve the appearance and features of the application tapp market in order to compete with applications that have been present before. In this research, diary study method is used to explore the experience and user response deeply and conceptually in the application of tapp market application. In addition to the use of the diary study method, a user journey method is used to map the user's journey in interaction with the application being researched to obtain user travel maps containing touchpoints and ideas for improvements from each stage run by the user. The problems found in this study related to the improvement of features and appearance. The results of recommended improvements to the look and features of the user's travel mapping are the basis for the improvement and creation of user protocols. Measures of success of this research process based on the validation of the expert to obtain data in accordance with the purpose of research.